2001
DOI: 10.1046/j.1365-2567.2001.01205.x
|View full text |Cite
|
Sign up to set email alerts
|

Perpetuation of immunological memory: a relay hypothesis

Abstract: SUMMARYA mechanism is proposed which explains the perpetuation of B-cell immunological memory inde®nitely without requiring the presence of long-living memory cells or persisting antigen. The salient feature of this model is that immunological memory can be perpetuated inde®nitely through the mutual interaction of idiotypic and anti-idiotypic B cells. These cells mutually stimulate and clonally expand with either speci®c or bystander T-cell help. Because B cells can present antigen, they present`apparently for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
36
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 35 publications
8
36
0
Order By: Relevance
“…9 and 10 suggest that the homeostatic turnover of a memory B cell depends on the antigen type and also on their mutation(s). Thus, our model aligns best with the earlier work of Nayak et al(2001) and Matzinger et al (1995), and it also aligns to some extent with the work of Tarlinton et al, specifically with respect to storage capacity (homeostatic turnover). However, our results do not line up with a hypothesis of randomness (stochastically) for the kinetics of immune memory, as inferred by Choo et al…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…9 and 10 suggest that the homeostatic turnover of a memory B cell depends on the antigen type and also on their mutation(s). Thus, our model aligns best with the earlier work of Nayak et al(2001) and Matzinger et al (1995), and it also aligns to some extent with the work of Tarlinton et al, specifically with respect to storage capacity (homeostatic turnover). However, our results do not line up with a hypothesis of randomness (stochastically) for the kinetics of immune memory, as inferred by Choo et al…”
Section: Discussionsupporting
confidence: 90%
“…8 indicate, in part, an alignment with the work of Choo et al(2010) and with that of Tarlinton et al, because some populations were "forgotten" so that others could be "memorized", thereby complying with the principle of homeostatic turnover. However, Tarlinton et al(2008) [49] and Choo et al (2010) [57] suggest that the mechanism for achieving homeostasis is stochastic, contrary to earlier work of Matzinger (1995) [50] and Nayak et al (2001) [19], who indicated that the durability of memory depends on the antigen type.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…We speculate that an antigen-independent memory could be generated by the interaction of GAD65Ab-specific B cells with complementary B cells that produce anti-Id (for review see ref. 44). Moreover, the anti-Ids explain previous evidence of a serum factor preventing the binding of autoantibodies to GAD65 observed by Brown and Christie (45).…”
Section: Discussionmentioning
confidence: 99%